2021
DOI: 10.1186/s13256-021-03156-y
|View full text |Cite
|
Sign up to set email alerts
|

Extensive bilateral diffuse infiltrates and deterioration of lung following infection with severe acute respiratory syndrome coronavirus 2 in a pregnant woman: a case report

Abstract: Introduction Severe acute respiratory syndrome coronavirus 2 is the third member of the coronavirus family to cause global concern in the twenty-first century. Pregnant women are particularly at higher risk of developing severe viral pneumonia, possibly because of a partial immune suppression during their pregnancy. Under such critical and rapidly evolving circumstances, these poor findings might be helpful for the treatment of infected pregnant women with the 2019 novel coronavirus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Viral load in the infected mother may be another contributing factor for the vertical transmission ( Qiu et al, 2020 ; Fan et al, 2021 ). Neonatal death due to COVID-19 was only reported in four cases throughout the studies in Iran ( Rashidian et al, 2020 ; Moeindarbary et al, 2021 ; Vizheh et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…Viral load in the infected mother may be another contributing factor for the vertical transmission ( Qiu et al, 2020 ; Fan et al, 2021 ). Neonatal death due to COVID-19 was only reported in four cases throughout the studies in Iran ( Rashidian et al, 2020 ; Moeindarbary et al, 2021 ; Vizheh et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…In one study, Eman [11] reported an ICU mortality rate of 42.1%, representing all eight COVID-19 pregnant patients who were intubated and mechanically ventilated. Lokken [3] and Moieindarbary [12] reported only one patient admitted to the ICU, who subsequently died of respiratory failure after a prolonged ICU stay despite multiple COVID-19 therapeutics, which is a 100% mortality rate. Lucovnik [6] reported a 33.33% mortality rate in critically ill pregnant patients.…”
Section: Introductionmentioning
confidence: 99%